Implant-supported double-bar overdenture to reestablish lip support in an atrophic maxilla: A case report - Longhini, Diogo [UNESP] (2018)
Prosthodontic treatment for edentulous maxillae with severe bone loss is a challenge to clinicians. Although implant-supported, fixed maxillary complete dentures are increasingly common, they are not always able to provide adequate lip support without a buccal overextension in patients with bone loss. The overextended buccal flange makes it difficult for patients to clean under the prosthesis. This case report describes rehabilitation of an atrophic maxilla through an implant-supported double-bar overdenture designed to resolve difficulties in oral hygiene maintenance that were caused by the buccal overextension of the prosthetic flange in a previous implant-supported fixed complete denture. In addition to reestablishing lip support, overdentures with a double-bar system provide retention and stability, because the prosthesis is only removed for cleaning by the patient with the help of a specific key. Implant-supported double-bar overdentures represent a viable and versatile option for rehabilitation of atrophic maxillae.